Measurement of the isotope shift of the 2p43P2⃗2p33p3P2 two-photon transition of O I and a revision of the triplet energy levels of atomic oxygen. (28th February 2017) - Marinov, D; Booth, J-P; Drag, C; Blondel, C
Abstract: Two-photon induced fluorescence of atomic oxygen, which is routinely used for plasma and flame diagnostics, is implemented with two counterpropagating laser beams of sufficient monochromaticity to permit Doppler-free spectroscopy. A single-mode injection-seeded pulsed Ti:sapphire laser has been frequency-doubled twice to produce narrow-band pulsed radiation at wavelengths around 225.6 nm, suitable to excite the ground-state-to- 2 p 3 3 p 3 P two-photon resonance line of oxygen. Accurate measurement of the injection-seeding wavelength provides new data on the excitation energy of the 3 p 3 P states. The experiment was done both sequentially and simultaneously on 16 O and 18 O, which makes it possible to test recent calculations of the isotope shift. Having an absolute measurement of the excitation wave-number from the ground level, which has been the case only twice in previous spectroscopic studies of O I, we can re-examine the energy levels of the subset of triplet states and present an updated set of optimised energy values.